A study on the Fe3O4@Fructus mori L. polysaccharide particles with enhanced antioxidant activity and bioavailability. Issue 3 (27th February 2020) - Zhang, Jia-Qi; Chen, Chun; Fu, Xiong; Liu, Rui-Hai
Abstract : Molecular conformation is closely related to the functional properties of macromolecules. Abstract : Molecular conformation is closely related to the functional properties of macromolecules. In order to prove that the bioactivity of mulberry fruit polysaccharides (MFPs) is greatly affected by the conformation, and to improve adsorption properties, we have designed Fe3 O4 @MFPNPs core–shell nanoparticles. The spherical Fe3 O4 @MFPNPs have been successfully synthesized with particle size distribution in the ranges of 3–10 nm and 68–164 nm, which are smaller than their previously prepared original polysaccharides and MFP-Fe(iii ). The Fe3 O4 @MFPNPs showed better antioxidant activity in comparison to MFP and MFP-Fe(iii ). The difference in the antioxidant activity between Fe3 O4 @MFPNPs and MFP-Fe(iii ), both of which were modified based on elemental iron, may be attributed to their different conformations: MFP-Fe(iii ) were rod-shaped, while Fe3 O4 @MFPNPs were spherical. Furthermore, Fe3 O4 @MFPNPs also exhibited greater absorption in the small intestine, which can promote its application in human health.